Receptive Aesthetic Criteria: Reader Comparisons of Two Finnish Translations of "Hamlet" - Keinänen, Nely (Multicultural Shakespeare: Translation, Appropriation and Performance, 2018)
This article examines the subjective aesthetic criteria used to assess two Finnish translations of Hamlet, one by Eeva-Liisa Manner (1981) and the other by Matti Rossi (2013), both accomplished translators for the stage. A survey consisting of one general question (“Briefly describe your idea of how Shakespeare translation should sound in Finnish, and what you think are the qualities of a good Shakespeare translation”) and five text extracts was distributed on paper and electronically, generating 50 responses. For the extracts, respondents were asked whether one or the other translation most closely dorresponded to their idea of what a Shakespeare translation should sound like and why, along with questions on whether they would prefer to see or read one or the other. The results show that there are no strong shared expectancy norms in Finland regarding Shakespeare translation. Manner was generally felt to be more concise and poetic, while Rossi was praised for his exquisite use of modern Finnish. Respondents agreed that rhythm was an important criterion, but disagreed on what sorts of rhythms they preferred. Translation of the “to be or not to be” speech raised the most passions, with many strongly preferring Manner’s more traditional translation. The results suggest that Shakespeare scholars would do well to take variations in expectancy norms into account when assessing and analysing Shakespeare in translation.